Iraq's Image in the British Press An analytical study of the Guardian and The Daily Telegraph for 1 / 1- 31/3/2019: Research extracted from a master's thesis - Morteza Mohammed Al-Gharabi, Samir; Ezzedine Abdul Razzaq, Noah (ALBAHITH ALALAMI, 2022)
The topic of the research dealt with the image of Iraq in the British press based on a sample of the newspapers (The Guardian and the Daily Telegraph), which are among the most important and largest newspapers in the United Kingdom and the world, because of its active role in guiding local and international public opinion towards important issues and events, Since these two newspapers are interested in the accuracy of sensitive political topics, the message aimed at knowing the media image that these two newspapers painted about Iraq in the period that was limited to the first quarter of 2019, and also to know the nature of the contents promoted by these newspapers about the Iraqi reality, The method of content analysis was used as an appropriate tool to describe the content and analyze it, indicate its links and indications and infer the answer to the objectives of the study, as well as the method of statistical analysis based on tables and classification of information, and then to obtain the desired results. The study showed that the two newspapers have been very interested in the issues of Iraqi affairs, if the Guardian newspaper preceded the Daily Telegraph with this interest and by a small margin by its surroundings (84) topics, while the number of topics for the Daily Telegraph reached (77), With a relative convergence of results, the Guardian has highlighted the issues concerning the presence of terrorist organizations represented by ISIS in Iraq, followed by political and diplomatic issues, and then the issues concerning military and security affairs, These classifications were somewhat similar to the Daily Telegraph with a disparity in salary hierarchy.